Preferences of Online Teaching and Learning Platforms - Perdana , Dyah Pitaloka Siwi (Jurnal Penelitian Mahasiswa Indonesia, 2022)
This study aims to identify teacher and students’ preferences of online teaching and learning platforms during the Covid-19 pandemic. This research is library research. The research studies carried out include research that has been carried out from 2020 to 2022. The five studies studied were mainly conducted in Indonesia. The results of this study found that the teacher's preference in teaching courage was to use zoom meetings and google classroom. The results of the study also revealed that the zoom meeting and google classroom were very easy to operate and really helped teachers in teaching boldly. The implementation of zoom meeting and google classroom is very flexible to help students understand the learning material.